Conceiving agency : reproductive authority among Haredi women - Raucher, Michal (Indiana University Press, 2020)
"Pregnancy and Agency among Haredi Women explores the ways Haredi Jewish women make decisions about their reproductive lives. Although they must contend with interference from doctors, rabbis, and the Israeli government, Haredi women find space for-and insist on-autonomy from them when they make decisions regarding the use of contraceptives, prenatal testing, fetal ultrasounds, and other reproductive practices. Drawing on their experiences of pregnancy, knowledge of cultural norms of reproduction, and theological beliefs, Raucher shows that Haredi women assert that they are in the best position to make decisions about reproduction. Pregnancy and Agency among Haredi Women puts forward a new view of Haredi women acting in ways that challenge male authority and the structural hierarchies of their conservative religious tradition. Raucher asserts that Haredi women's reproductive agency is a demonstration of women's commitment to Haredi life and culture as well as an indication of how they define religious ethics"--